The role of single nucleotide polymorphisms of NFATC genes in the development of left ventricular hypertrophy in primary arterial hypertensive adolescents - A.V. Tovma; A. M. Kamyshnyi; A. V. Kamenshchyk; O. G. Ivanko (Zaporozhye State Medical University, 2017)
The aim of the study was to determine the possibility of association of the single nucleotide polymorphisms (SNP) of NFATC1 and NFATC4 genes with the development of concentric hypertrophy of the left ventricle (LVH) in adolescents aged 16-18 with newly diagnosed primary hypertension (AH). Material and methods. The study included 74 adolescents aged 16-18 years (50 boys and 24 girls) who for the first time in the course of preventive medical examination were identified as primary hypertensive carriers. According to the echocardioscopy (Echo-CS) the concentric hypertrophy of the left ventricle was shown in 32 (43%) of adolescents. Other 42 (57%) young people with AH were identified as a control group because their Echo-CS and еlectrocardiography (ECG) data were within the age limits. At the next stage of the study for all the patients the genotyping by a standard PCR method in a real time was performed using samples of total DNA isolated from the whole venous blood. Results. As shown by the results of genotyping and statistical analysis SNP association with LVH was detected in relation to rs2229309 of the NFATC4 gene and not confirmed for SNP (rs7240256, rs11665469, rs754505) of the NFATC1 gene. Statistically significant differences of incidence (p <0.05) were found for the heterozygous genotype status of this SNP which is almost 2 times more common for adolescents with primary hypertension complicated with early LVH. Predictive significance of the sign "heterozygous genotype CG rs2229309 of the NFATC4 gene" for the development of concentric LVH in adolescents aged 16-18 with primary hypertension was sensitive in 46%, specific in 74% and accurate in 62% of cases. The odds ratio of development of concentric LVH in the adolescents with the detected symptom was 2.43 with the 95% confidence interval of 0.78 to 7.58. At the same moment the predominance of the G allele in these adolescents also was established. Conclusions. There is an obvious association between the heterozygous condition of CG rs2229309 of NFATC4 gene and early LVH development in adolescents with primary arterial hypertension, diagnosed at the age of 16-18. Also this people are prone to be carriers of the G allele. The genotyping of rs2229309 of the NFATC4 gene can be useful in prognosis of the risk of LVH development in adolescents with AH.